Validitas dan reliabilitas tes pengukuran keterampilan pemain futsal - Susworo Dwi Marhaendro, Agus; Suharjana, Suharjana; Sujarwo, Sujarwo (Universitas Nusantara PGRI Kediri, 2023)
This study tested the validity and reliability of the Futsal Skill Test (FST) for student actors. Twenty-four futsal players from the university's futsal team comprised men's (n=12) and women's (n=12) teams. The Futsal Skill Test (FST) is carried out on the futsal field and checks skills such as passing, controlling, dribbling, and shooting the ball as quickly as possible by making the minimum possible mistakes. The validity of the content is assessed using experienced futsal trainers and instructors. Data analysis in validity measurements was determined using known group differences between male and female university futsal players, then reliability was determined using Pearson's correlation coefficient (r), intraclass correlation coefficient (ICC), and variation coefficient (CV) between experimental repeats. The results showed that the variance equivalence test on Performance Time (Time Taken and Penalty Time) showed that F had been 0.048 (0.013 and 0.375) with a significance of 0.829 (0.910 and 0.547). Performance Time for men is different from that of female university players. T-test results for the quality of the means for Performance Time (Time Required and Penalty Time) t=-5.506 p=0.000 (t=-5.5277 p=0.000 and t=-2.060 p=0.051). The CV Time Taken, Penalty Time and Performance Time scores for male students were 6.97%, 28.46%, and 6.88%, for female students, were 6.81%, 19.63%, and 6.38%, both for male and female students were 6.89%, 24.04%, and 6.63%. The FST assessment is an apt score to describe the performance time, that the player with the faster time achieved from the futsal skill Test is more skilled. The Performance Time score consists of Time Taken and Penalty Time.